2021
DOI: 10.1111/1346-8138.15771
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for readmission due to cellulitis among Japanese patients

Abstract: Cellulitis is a skin and soft tissue infection that is accompanied by symptoms, such as swelling, flushing, and pain [1]. The main causative bacterial species are group A β-Streptococcus and Staphylococcus aureus [2]. Some patients, especially those with chronic swelling (lymphedema), obesity, and diabetes, are at an increased risk of cellulitis [1,3]. Previous studies have reported that 41% to 45.3% of cellulitis cases eventually recur [4].A recurrence prediction score for the cellulitis of the lower limbs ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 11 publications
0
15
1
Order By: Relevance
“…In contrast it is unclear why hyperlipidemia is associated with the recurrence of cellulitis in the Japanese population 4 . Oxidized LDL (ox-LDL) is known to activate dendritic cells (DCs) in hyperlipidemia 7 .…”
Section: Dear Editormentioning
confidence: 98%
See 3 more Smart Citations
“…In contrast it is unclear why hyperlipidemia is associated with the recurrence of cellulitis in the Japanese population 4 . Oxidized LDL (ox-LDL) is known to activate dendritic cells (DCs) in hyperlipidemia 7 .…”
Section: Dear Editormentioning
confidence: 98%
“… 3 In addition, LVA, as a treatment of lymphedema, might also prevent the recurrence of cellulitis. In contrast, Norimatsu and Ohno 4 reported that hyperlipidemia, hypertension, hypoalbuminemia, and lymphedema are significant risk factors for recurrent cellulitis in the Japanese population. Hypoalbuminemia, in particular, is a risk factor in the Japanese population.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…However, the risk factors for recurrent cellulitis are reportedly different from those in other countries due to the different characteristics of Japanese patients [9].…”
Section: Introductionmentioning
confidence: 94%